Factors influencing zakat on income behaviour among the muslim community in Selangor / Nur Ellyana Syafiqa Nazarudin - Nazarudin, Nur Ellyana Syafiqa (Faculty of Business Management, 2018)
Nowadays, the lack of motivation of zakat on income behaviour among Muslims was needed for care and serious attention as zakat was an obligatory for Muslims. Issues on collections of zakat on income arise every year due to a lower total of collections compared with total collections on income tax year by year. According to (Ahmad & Hairunnizam Wahid, 2005), there are seven categories of group who pay zakat which are a group of payer if there is any act or law which is mandatory to pay, a group of people who pay income tax rather than zakat income, a goup of people who are not paying zakat because of having no knowledge, a group of people who have too much question on the obligatory of zakat payment, a goup of people who assume that zakat is burden and a goup of people who assume it is only zakat Fitrah. As mentioned on the issue arises, Muslims has intended to pay income tax rather than zakat because they have assumed that when they pay income tax, automatically there is no need for contribution in zakat payment. This confusion was believed to be still happening until today. The objective of the study is to seek for factors influencing zakat on income behaviour among the Muslim community in Selangor. Data was collected using questionnaires and analysed by Factor Analysis and regression from SPSS. The findings were result three from independent variables was significant which are organizational factor, reward and self-satisfaction.